Photosynthetic acclimation of coffee in response to water availability and fruiting: a hydraulic and hormonal approach - Almeida, Wellington Luiz de (2018)
The overall coordination between gas exchanges and plant hydraulics may be affected by the soil availability of water and source-to-sink relationships. Here we evaluated how coffee (Coffea arabica L. cv. Catimor) trees are able to acclimate their photosynthesis in response drought and fruiting. The plants, which were 6-yr- old at the beginning of trials, were grown in the field at full sunlight, and subjected to four treatment combinations: irrigated plants with fruits (I*F); irrigated plants with no fruits (I*NF); non-irrigated plants with fruits (NI*F) and non-irrigated plants with no fruits (NI*NF). A range of traits, encompassing from photosynthesis traits, water relations, growth and hormonal profile, were assessed. Over the course of the experiment, the non-irrigated plants displayed lower averaged values of predawn water potentials (-0.5 MPa) than their irrigated counterparts (-0.2 MPa). We showed that under mild water deficit conditions, irrigation per se did not impact growth rates but could reduce branch death significantly. These findings were unrelated to changes in leaf assimilate pools. We also demonstrated that fruiting provoked a feedforward effect on net photosynthesis rate that was fundamentally coupled to an enhanced stomatal conductance. Indeed both the mesophyll conductance and maximum rate of carboxylation by RuBisCO remained unchanged in response to the applied treatments. The increase in stomatal conductance was unrelated to varying abscisic acid levels or differential sensitivity to abscisic acid, although it was likely associated with a lower stomatal sensitivity to leaf-to-air vapor pressure difference. In parallel, the increases in transpiration rate were supported by coordinated alterations in plant hydraulics which should to a large extent explain the maintenance of plant water status regardless of fruiting-related variations in stomatal conductance and transpiration rate. In summary, we showed that stomatal conductance played a major role in the coordination between source capacity and sink demand regardless of irrigation, with concomitant changes in plant hydraulics. Therefore, these aspects should be considered in breeding programs to improve drought tolerance in coffee in face of the present and ongoing climate changes.